Gesammelte Aufsätze zur altfranzösischen Epik - Adolf Beckmann, Gustav (De Gruyter Collection, 2019)
Conceived as a companion volume to his Onomastics of the Song of Roland (2017), Beckmann's eighteen Collected Essays on Old French Epic Poetry presents a multi-faceted panorama about the origins of the ancient chansons de geste. It includes the chansons of Ogier, Roland, William (Guillaume), Saxon epic poetry, the Pilgrimage of Charlemagne and Berthe with the Big Feet, and Renaut de Montauban.